2021
DOI: 10.3390/ijerph18041475
|View full text |Cite
|
Sign up to set email alerts
|

Driver Liability Assessment in Vehicle Collisions in Spain

Abstract: An accurate estimation of exposure is essential for road collision rate estimation, which is key when evaluating the impact of road safety measures. The quasi-induced exposure method was developed to estimate relative exposure for different driver groups based on its main hypothesis: the not-at-fault drivers involved in two-vehicle collisions are taken as a random sample of driver populations. Liability assignment is thus crucial in this method to identify not-at-fault drivers, but often no liability labels ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
(107 reference statements)
0
3
0
2
Order By: Relevance
“…Around the world, researchers are working on alternative means of elicitation, exploring new data sources, and in the Quasi-Induced Exposure (QIE) methodology, from data contained in accident databases. In the paper [81], they have developed a methodology for improving driver crash liability useful for the QIE approach. In addition, in research papers, it can be found that the age is a factor to be taken into account.…”
Section: Data Descriptive and Regression Analysis By Joinpoint Resultsmentioning
confidence: 99%
“…Around the world, researchers are working on alternative means of elicitation, exploring new data sources, and in the Quasi-Induced Exposure (QIE) methodology, from data contained in accident databases. In the paper [81], they have developed a methodology for improving driver crash liability useful for the QIE approach. In addition, in research papers, it can be found that the age is a factor to be taken into account.…”
Section: Data Descriptive and Regression Analysis By Joinpoint Resultsmentioning
confidence: 99%
“…Así, por ejemplo, el clúster 15 contiene un total de 30.729 conductores, mientras que en el clúster 23 no hay ningún conductor. Un análisis más detallado puede encontrarse en Sanjurjo- de-No et al (2021).…”
Section: Resultsunclassified
“…Por tanto, basándonos en las hipótesis planteadas, se escogió el valor de 0,25 para los casos en los que se desconocía el valor de la variable. Más información puede encontrarse en Sanjurjo- de-No et al (2021).…”
Section: Materials Y Métodosunclassified
“…Despite the results presented here, and the importance of personality in affecting driving behaviors, self-reported personality measures should be considered with caution [ 108 ] considering their exposure to faking good, especially in forensic assessments in which they could potentially lead to paradoxical effects. Furthermore, these results may be a relevant source of knowledge for researchers dealing with both the prediction of motor vehicle-crashes and the driver’s liability in such events [ 109 ], providing information about variables that are able in detecting drinker drivers.…”
Section: Discussionmentioning
confidence: 99%